Pengaruh Kualitas Pelayanan dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Di Samsat Kelapa Dua Kabupaten Tangerang - Hana Fujiana; Juliannes Cadith; Sierfi Rahayu (Public Policy and Management Inquiry, 2026)
This study aims to determine the influence of service quality and tax sanctions on taxpayers' compliance in paying motor vehicle taxes in Samsat Kelapa Dua, Tangerang Regency. This study uses a quantitative method with an associative approach. The sampling technique is purposive sampling based on certain criteria (taxpayers who pay motor vehicle taxes directly at Samsat Kelapa Dua, Tangerang Regency). Data collection techniques with questionnaires (Google form and in person), interviews, documentation, and literature studies. Data processing was carried out with the help of SPSS 29 (Statistical Program for Social Sciences) using the multiple linear regression test method to determine the influence of two or more independent variables on the bound variables. The results of this study show that the quality of service and tax sanctions have a significant effect on taxpayer compliance. Based on the results of the analysis, there is an influence of service quality on taxpayer compliance by 71.0%, of the service quality variable that can affect taxpayer compliance is a guarantee indicator. There was no effect of tax sanctions on taxpayer compliance by 46.5%, from the variable tax sanction indicator that sanctions were carried out strictly with the highest score that increased taxpayer compliance. There is an influence between service quality, tax sanctions on taxpayer compliance by 71.9%, from the taxpayer compliance variable indicator that fulfills obligations that most affects taxpayer compliance. Suggestions to overcome this problem are to provide facilities that are not yet available, publish the latest information related to Samsat services, Samsat must be responsive in responding to complaints from taxpayers. Providing socialization about the importance of paying taxes and socialization related to tax sanctions so that taxpayers understand the purpose of sanctions and the imposition of sanctions on taxpayers who do not carry out their tax obligations.